Analisis Perbandingan Penentuan Harga dalam Pemikiran Adam Smith dan Karl Marx - Mica Siar Meiriza; Endang Endang; Fera Daniaty Nababan; Putri Titin Sianturi (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
The aim of this research is to find out how price determination in Adam Smith's thinking compares with Karl Marx's thinking. The research method used in this research is a literature review by analyzing a number of articles and magazines related to the thoughts of Adam Smith and Karl Marx. We get all kinds of data through relevant assessments. The results of this research are that according to the thoughts of Adam Smith, one of the figures of Capitalism, determining prices in the free market, market prices are determined by the power of the market mechanism called the "law of supply and demand". Meanwhile, according to the thoughts of Karl Marx, who is a figure of Marxism, it is different from Adam Smith's thoughts that the price of a good or service is determined by the amount of labor needed to produce it.